The Coming of Age of Preclinical Models of MDS - Liu, Wei; Teodorescu, Patric; Halene, Stephanie; Ghiaur, Gabriel (Frontiers in Oncology, 2022)
Myelodysplastic syndromes (MDS) are a heterogeneous group of clonal bone-marrow diseases with ineffective hematopoiesis resulting in cytopenias and morphologic dysplasia of hematopoietic cells. MDS carry a wide spectrum of genetic abnormalities, ranging from chromosomal abnormalities such as deletions/additions, to recurrent mutations affecting the spliceosome, epigenetic modifiers, or transcription factors. As opposed to AML, research in MDS has been hindered by the lack of preclinical models that faithfully replicate the complexity of the disease and capture the heterogeneity. The complex molecular landscape of the disease poses a unique challenge when creating transgenic mouse-models. In addition, primary MDS cells are difficult to manipulate ex vivo limiting in vitro studies and resulting in a paucity of cell lines and patient derived xenograft models. In recent years, progress has been made in the development of both transgenic and xenograft murine models advancing our understanding of individual contributors to MDS pathology as well as the complex primary interplay of genetic and microenvironment aberrations. We here present a comprehensive review of these transgenic and xenograft models for MDS and future directions.